Evaluative Adjectives are Davidsonian States - Fábregas, Antonio; Leferman, Bryan; Marín, Rafael (Proceedings of Sinn und Bedeutung, 2019)
The aspectual properties of evaluative adjectives (EAs), such as brave and cruel, have been the object of a vivid debate, as they pattern with individual-level predicates (ILP) with respect to the interpretation of bare subjects and their inability to function as depictive adjuncts but, like stage-level predicates, they can have an episodic reading. In addition to this, among adjectives they exhibit exceptional aspectual properties, such as taking the progressive. In this paper, we concentrate on EAs in English and Spanish and argue that they can be characterised as Davidsonian-states, that is, stative event predicates. However, since EAs alternate clearly between two distinct readings–suggesting that the event is not part of the adjective’s lexical entry (unlike D-state verbs such as sleep or wait)–we analyze them as ILPs with the ability to predicate of two sorts of subject: an individual or an event. In the first case they behave like ILPs, in the second they exhibit all the aspectual properties associated with eventive predicates.